The new English A Levels 2015: a guide to the specs - Cushing, Ian; Giovanelli, Marcello; Snapper, Gary (National Association for the Teaching of English (NATE), 2015)
Ian Cushing, Marcello Giovanelli and Gary Snapper summarise the changes at A Level from September 2015 and explore the features of each of the new specs in all three A Level English subjects.